Etnoornitologia no Povoado de Pedra Branca, município de Santa Teresinha, Bahia - Loss, Ana Teresa Galvagne (2013)
The ethnoornitology seeks to understand the relationships cognitive, behavioral and symbolic between humans and birds, and they through popular names, uses, legends and beliefs.The present study investigated Pedra Branca, municipality of Santa Teresinha, Bahia, inhabitants’ local knowledge about the local ornitofauna, pointing behavioral and ethnotaxonomical aspects, investigating birds’ local uses and consequential impacts. Data collection was conducted through semi-structured interviews, participant observation and projective test with presentation of audio-visual material for ethnospecies identification. A total of 48 inhabitants, both men and women, were interviewed. As results, 144 common names were registered, which are dispersed in 109 ethnospecies and 35 synonymies, concerning 112 scientific species. The most used nomenclatural criteria for naming birds were vocalization and staining model. Three ethnobiological hierarchical ranks were recorded: way of life, generic and specific, occurring three types of correspondence between academic’s system classification and folk. In Pedra Branca birds are used for a variety of purposes such as food, folk medicine, as a pet and trade, six methods of hunting these animals recorded to capture. The species most used as trophic resource belong to Tinamidae, Columbidae and Cracidae families; trap, rifle, dog and pious as most used hunting tools to capture. In folk medicine, the chicken (Gallus gallus), the black vulture (Coragpis atratus), zabele (Crypturellus noctivagus) and duck (Cairina moschata) were the most cited ethnospecies. Regarding pet birds, the family Emberizidae was recorded with greater representation, but the family was the most cited Thraupidae, having Estevo (Saltator similis) as species of greatest local interest.The ethnoornitology research in Pedra Branca allowed contribute to new information about the popular nomenclature of birds as well as record the use evidence two endangered species.